A Framework for Evaluating Science and Technology Electronic Reference Books: A Comparison of Five Platforms in Chemistry. - Meghan Lafferty (Issues in Science and Technology Librarianship)
This article examines what is desirable in online reference books in science and technology and outlines a framework for evaluating their interfaces. The framework considers factors unique to these subject areas like chemical structures and numerical data. Criteria in three categories, navigability, searchability, and results, were applied to five key chemistry e-resources. Some e-book publishers are taking e-books farther and changing expectations for the rest. The framework offers a guide for holding publishers accountable for developing e-reference books that meet users' needs. [ABSTRACT FROM AUTHOR]